2013
DOI: 10.1016/j.neuropsychologia.2013.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal subcortical components of the corticostriatal system in young adults with DLI: A combined structural MRI and DTI study

Abstract: Developmental Language Impairment (DLI) is a neurodevelopmental disorder affecting 12% to 14% of the school-age children in the United States. While substantial studies have shown a wide range of linguistic and non-linguistic difficulty in individuals with DLI, very little is known about the neuroanatomical mechanisms underlying this disorder. In the current study, we examined the subcortical components of the corticostriatal system in young adults with DLI, including the caudate nucleus, the putamen, the nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 91 publications
5
44
0
Order By: Relevance
“…This neural network involves a variety of human behaviors, including acquisition of habits, learning of sequence and categorization, working memory function, and reinforcement learning (Koziol & Budding, 2009). Previous studies showed that individuals with DLD have difficulty with different types of procedural learning as well as reinforcement learning (Lee & Tomblin, 2012, 2015; Lum & Conti-Ramsden, 2013; Ullman & Pierpont, 2005), which is consistent with brain imaging findings showing structural and functional alterations in the corticostriatal pathways of DLD (Badcock et al, 2012; Jernigan et al, 1991; Lee, Nopoulos, & Tomblin, 2013; Soriano-Mas et al, 2009). …”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…This neural network involves a variety of human behaviors, including acquisition of habits, learning of sequence and categorization, working memory function, and reinforcement learning (Koziol & Budding, 2009). Previous studies showed that individuals with DLD have difficulty with different types of procedural learning as well as reinforcement learning (Lee & Tomblin, 2012, 2015; Lum & Conti-Ramsden, 2013; Ullman & Pierpont, 2005), which is consistent with brain imaging findings showing structural and functional alterations in the corticostriatal pathways of DLD (Badcock et al, 2012; Jernigan et al, 1991; Lee, Nopoulos, & Tomblin, 2013; Soriano-Mas et al, 2009). …”
Section: Introductionsupporting
confidence: 87%
“…I hypothesized that compared with those without DLD, adolescents with DLD would be insensitive to response-contingent feedback, resulting in abnormal risk taking behavior on the BART. While there is no prior work on response-contingent feedback in DLD, this hypothesis is generated from previous studies showing poor feedback-based learning as well as structural abnormality of the nucleus accumbens in DLD (Kemeny & Lukacs, 2010; Lee & Tomblin, 2012; Lee et al, 2013). As an ancillary analysis, the BIS/BAS scales were used to evaluate a person’s response to reward-related or punishment-related events in daily situations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, individuals with developmental language impairment, a disorder characterized by deficits in morphosyn-tactic components of language that are thought to be acquired through statistical learning (Evans et al, 2009), demonstrate significant correlations between hippocampal volume and language measures in this population (Lee, Nopoulous, & Tomblin, 2013). These data, together with work by Turk-Browne and colleagues as well as the work presented here, provide a challenge to proposed divisions of labor for hippocampus (vocabulary) and BG (grammar) in language processing (Ullman, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In a more general manner, GP has been shown to be activated during speech production tasks (Klein et al 2006;Riecker et al 2000;Wise et al 1999) and several studies have demonstrated that this structure is relevant for verbal fluency (Schmand et al 2000;Whelan et al 2004;York et al 2003). In addition, abnormalities in activity and structure of GP have also been reported in language-related disorders, such as Developmental Language Disorder (Hwang et al 2006;Lee, Nopoulos, Bruce Tomblin 2013;Ors et al 2005) and children with speech sound errors (Preston et al 2012). Therefore, the results observed here for the globus pallidus further support the possibility that morphological differences between bilinguals and monolinguals are related to an array of subcortical structures involved in language production, ranging from articulatory, low-level motor structures to regions involved in lexico-semantic monitoring.…”
Section: Discussionmentioning
confidence: 99%